The Effects of Physical Fitness and Body Composition on Oxygen Consumption and Heart Rate Recovery After High-Intensity Exercise - Campos, E. Z. [UNESP]; Bastos, F. N.; Papoti, M. [UNESP]; Freitas Junior, I. F. [UNESP]; Gobatto, C. A.; Balikian Junior, Pedro [UNESP] (Georg Thieme Verlag Kg, 2012)
The aim of this study was to investigate the potential relationship between excess post-exercise oxygen consumption (EPOC), heart rate recovery (HRR) and their respective time constants (tvo(2) and t(HR)) and body composition and aerobic fitness (VO(2)max) variables after an anaerobic effort. 14 professional cyclists (age = 28.4 +/- 4.8 years, height = 176.0 +/- 6.7 cm, body mass = 74.4 +/- 8.1 kg, VO(2)max = 66.8 +/- 7.6 mL. kg(-1) . min(-1)) were recruited. Each athlete made 3 visits to the laboratory with 24h between each visit. During the first visit, a total and segmental body composition assessment was carried out. During the second, the athletes undertook an incremental test to determine VO(2)max. In the final visit, EPOC (15-min) and HRR were measured after an all-out 30s Wingate test. The results showed that EPOC is positively associated with % body fat (r = 0.64), total body fat (r = 0.73), fat-free mass (r = 0.61) and lower limb fat-free mass (r = 0.55) and negatively associated with HRR (r = - 0.53, p < 0.05 for all). HRR had a significant negative correlation with total body fat and % body fat (r = - 0.62, r = - 0.56 respectively, p < 0.05 for all). These findings indicate that VO(2)max does not influence HRR or EPOC after high-intensity exercise. Even in short-term exercise, the major metabolic disturbance due to higher muscle mass and total muscle mass may increase EPOC. However, body fat impedes HRR and delays recovery of oxygen consumption after effort in highly trained athletes.
Keywords: excess post-oxygen consumption; aerobic fitness; heart rate recovery; cyclist; DXA